Special technical report on the effects of tropical cyclone freddy on the Ukama Ustawi trials in the Malawi south - Gama, Mphatso Samuel (International Maize and Wheat Improvement Center, 2023)
Nearly 154,816 farm families i.e., 59,718 male-headed households and 95,098 female-headed households have been affected by Cyclone Freddy through collapsed buildings, flooded and washed away crop fields, and killing or injuring livestock. An estimated crop area of about 56129.46 ha has been affected. The Cyclone did not spare our Ukama Ustawi Trials such that trials especially 32 out of 150 babies were submerged in water while the Innovation Trial in Songani Site in Zomba as the worst hit. Cyclone Freddy had a negative impact worthy of noting in Zomba District than the other districts. Soon after Cyclone Freddy, the Agriculture Sector in all the four affected District Councils undertook rapid assessment to establish the type of loss and damage, severity and suggested interventions that would assist in mitigation of effects of the Cyclone amongst the affected communities. This report covers, weather and its effects on crops and livestock, damages on crops and livestock, challenges, and general recommendations.